What's wrong with postmodernism critical theory and the ends of philosophy - Norris, Christopher 1947- (Baltimore, Maryland The Johns Hopkins University Press, 1990)
In What's Wrong with Postmodernism Norris critiques the "postmodern-pragmatist malaise" of Baudrillard, Fish, Rorty, and Lyotard. In contrast he finds a continuing critical impulse -- an "enlightened or emancipatory interest" -- in thinkers like Derrida, de Man, Bhaskar, and Habermas. Offering a provocative reassessment of Derrida's influence on modern thinking, Norris attempts to sever the tie between deconstruction and American literary critics who, he argues, favor endless, playful, polysemic interpretation at the expense of systematic argument.
Deconstruction, postmodernism and philosophy : Habermas on Derrida -- Right you are (if you think so) : Stanley Fish and the rhetoric of assent -- Limited think : how not to read Derrida -- Lost in the funhouse : Baudrillard and the politics of postmodernism -- Derrida and Kant -- Music, language and the sublime -- Settling accounts : Heidegger, de Man and the ends of philosophy.
Includes bibliographical references and index.
Keywords: Postmodernism; Literature -- Philosophy; Methodology